Agronomist goes to cinema - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Could an agronomist ever become the centre of world media attention? Oh yes. A film called The Agronomist: A Work in Progress caused quite a stir during the opening days of the Miami International Film Festival in the United States in February....